Protocol and pipeline for identifying superior cross-bred dairy bulls for use in smallholder farming systems, including via the use of genomics - CGIAR Research Program on Livestock (2019)
Protocol has been developed and various analytical models incorporating genomic information tested for identifying superior cross-bred dairy bulls for use in smallholder farming systems.